A critical review on machine-learning-assisted screening and design of effective sorbents for carbon dioxide (CO2) capture - Yang, Zequn; Chen, Boshi; Chen, Hongmei; Li, Hailong (Frontiers in Energy Research, 2023)
Graphical Abstract